Vocal repertoire of the Eurasian griffon vulture (Gyps fulvus) in the central Apennines: a baseline assessment. Issue 3 (4th May 2022) - Romani, Federico; Ramella Levis, Elena; Posillico, Mario; Opramolla, Giancarlo; Pavan, Gianni
ABSTRACT: The Eurasian griffon vulture ( Gyps fulvus ) represents an exception among the European accipitrids, as it forms highly populated colonies. Although it has been the subject of many studies, social interactions and intraspecific communication are still relatively unexplored. Because of its social habits, we hypothesise that the sound language of the griffon vulture is far more complex than previously believed; the 'Social Intelligence Hypothesis' could in fact be relevant to this species. In this study, we took as a model the vulture population of the central Apennines (Italy), comparing the vocalisations recorded in three different locations: (i) supplementary feeding station; (ii) nesting and roosting cliffs far from anthropogenic disturbance; (iii) nesting and roosting cliffs close to settlements and roads. The results obtained by 80 monitoring hours and 20 recording hours show an articulated vocal repertoire, characterised by 12 sound categories associated with different age groups and possibly to very specific behavioural contexts. The vocal repertoire is also marked in some cases by nonlinear phenomena revealing different degrees of behavioural complexity related to the expression of emotional states and social interactions. The next steps will focus on individual recognition mechanisms and the interactions with other species sharing part of the same ecological niche.